Molecular cloning and expression analyses of porcine MAP1LC3A in the granulosa cells of normal and miniature pig - Kim Sang H; Hwang Sue Y; Min Kwan S; Yoon Jong T (BMC, 2013)
Abstract Background The members of the microtubule-associated protein 1 light chain (MAP1LC) family, especially those of the LC3 family (MAP1LC3A, B, C), are known to induce autophagy upon localization onto the autophagosomal membrane. In this regard, LC3 can be utilized as a marker for the formation of autophagosomes during the process of autophagy. The aims of this study are to clone porcine MAP1LC3A, and analyze the pattern of its expression in the ovarian tissues of normal and miniature pig ovary in an attempt to understand the distinct mode of apoptosis between two strains. Methods Rapid amplification of cDNA ends (RACE) were used to obtain the 5' and 3' ends of the porcine MAP1LC3A full length cDNA. Reverse-transcriptase-PCR (RT-PCR), real-time PCR, and western blot analysis were performed to examine the expression of porcine MAP1LC3A. The localization of MAP1LC3A in the ovary was determined by In situ Hybridization and Immunohistochemical staining. Results We cloned the full-length cDNA of porcine MAP1LC3A and identified an open reading frame of 980 bp encoding 121 amino acids. Based on its homology to known mammalian proteins (98%) this novel cDNA was designated as porcine MAP1LC3A and registered to the GenBank (Accession No. GU272221). We compared the expression of MAP1LC3A in the Graafian follicles of normal and miniature pigs by in situ hybridization at day 15 of the estrus cycle. While normal pigs showed a stronger expression of MAP1LC3A mRNA than miniature pigs in the theca cell area, the expression was lower in the granulosa cells. Immunofluorescence analysis of the MAP1LC3A fusion reporter protein showed the subcellular localization of porcine MAP1LC3A and ATG5 as a punctate pattern in the cytoplasm of porcine granulosa cells under stress conditions. In addition, the expressions of MAP1LC3A and ATG5 were higher in normal pigs than in miniature pigs both in the presence and absence of rapamycin. Conclusions The newly cloned porcine MAP1LC3A provides a novel autophagosomal marker in both normal and miniature pig. We demonstrated that the expression of MAP1LC3A in graafian follicle is distinct in normal and miniature pig, which may explain the unique folliculogenesis of miniature pigs.